2017
DOI: 10.1111/ijfs.13634
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of polylactic acid–gliadin bilayer/trilayer films as carriers of thymol

Abstract: Summary Biodegradable food packaging promises a more sustainable future. Poly(lactic acid) (PLA) is a promising alternative for petroleum‐derived polymers. However, PLA films suffer from poor barrier properties compared with petroleum‐derived ones. To address this issue, we designed bilayer and sandwich‐architectured trilayer films based on PLA and gliadin. We reported firstly the direct formation of PLA–gliadin bilayer/trilayer films without surface modification on PLA film. The films were compact and uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…The authors indicated a highly confined release for gallic acid due to the presence of top polylactic acid layers. Similar to our study, the external layers acted as a barrier to the release of gallic acid [46] found a slower release of thymol from polylactic acid and gliadin based trilayer films, which might be due to the barrier effect of the polylactic acid layer.…”
Section: Release Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…The authors indicated a highly confined release for gallic acid due to the presence of top polylactic acid layers. Similar to our study, the external layers acted as a barrier to the release of gallic acid [46] found a slower release of thymol from polylactic acid and gliadin based trilayer films, which might be due to the barrier effect of the polylactic acid layer.…”
Section: Release Studiessupporting
confidence: 88%
“…Similarly, Zhu et al [46] found a slower release of thymol from polylactic acid and gliadin based trilayer films, which might be due to the barrier effect of the polylactic acid layer.…”
Section: 4mentioning
confidence: 88%
See 1 more Smart Citation
“…Another way to improve the WVP is presented by Zhu J.Y. et al, who have obtained bi and tri-layer films from PLA and gliadin, without surface modification [ 158 ]. These films have a good mechanical resistance, do not exfoliate, and most important, the gliadin improves the barrier properties of the PLA toward oxygen, while the PLA improves the barrier properties of gliadin toward water vapor.…”
Section: Biodegradable Polymeric Antimicrobial Packagingmentioning
confidence: 99%
“…Hydrogels are three-dimensional cross-linked polymer networks, which can absorb large amounts of water (Ahmed, 2015). These networks maintain their structure during the exchange of water and provide controlled release via pores in the polymer network (Zhu et al, 2018). Hydrogels based on polysaccharides, like chitosan and pectin, have been increasingly utilised in various fields (Kwiecie n & Kwiecie n, 2018).…”
Section: Introductionmentioning
confidence: 99%